2004
DOI: 10.1002/fuce.200400010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Effect of Flow Bed Design on Performance of Liquid Feed Direct Methanol Fuel Cells

Abstract: The effect of flow bed design on the performance of a liquid feed direct methanol fuel cell was studied experimentally. The flow beds were designed and manufactured with different channel densities, channel depths, and ridge widths. The flow beds were machined on stainless steel polar plates. The experimental results showed that ridge width affects the slope of the ohmic polarization curve. A ridge width of 3.30 mm provided the highest peak power. When the contact surface area between the flow bed and electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…They found that the flow field design significantly affected the heat and mass distribution and the output performance. [8][9][10][11][12][13][14][15] In previous researches, studies on flow field designs just focused on the two-dimensional space. What was changed was just on the two-dimensional (2D) plane on the flow field plate, and nothing was changed in the direction which was vertical to the surface of gas diffusion layers (GDLs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the flow field design significantly affected the heat and mass distribution and the output performance. [8][9][10][11][12][13][14][15] In previous researches, studies on flow field designs just focused on the two-dimensional space. What was changed was just on the two-dimensional (2D) plane on the flow field plate, and nothing was changed in the direction which was vertical to the surface of gas diffusion layers (GDLs).…”
Section: Discussionmentioning
confidence: 99%
“…where λ is the water content in the proton exchange membranes (Equation 10) and D 0 w−M is the initial water diffusion coefficient in the proton exchange membranes, which is expressed as Equation 11:…”
Section: The Gas Used In This Work Is Incompressible Becausementioning
confidence: 99%
See 1 more Smart Citation
“…Our previous experimental study had reported the side-view observation method in details. 32 In previous studies, numerous of previous publications had utilized the transparent plates to observe the gas-liquid two-phase flow inside PEMFCs, for example, the references, 2,3,24,25 etc. In addition, CHOI H et al 33 also utilized the transparent plates at PEMFCs to observe the water flooding phenomenon inside the cell.…”
Section: Introductionmentioning
confidence: 99%
“…In a PEMFC, whatever in a normal gravity condition or low gravity condition, the pressure drop and liquid water distribution are key issues that affect the electrochemical reactions in CLs 6 . The flow field design significantly impacts the reactants and products transportation in flow channels and gas diffusion layers (GDLs) 7 . The conventional flow field structure designs were just on the flow channels arrangement, and the cross‐section areas of them were rectangular, such as the serpentine flow field, cascade flow field, paralleled flow field, and interdigitated flow field.…”
Section: Introductionmentioning
confidence: 99%